2019
DOI: 10.1103/physrevd.100.034030
|View full text |Cite
|
Sign up to set email alerts
|

Landau-Pomeranchuk-Migdal effect in sequential bremsstrahlung: From large- N QCD to N=3 via the SU(

Abstract: Consider a high-energy parton showering as it traverses a QCD medium such as a quark-gluon plasma. Interference effects between successive splittings in the shower are potentially very important but have so far been calculated (even in idealized theoretical situations) only in soft emission or large-N c limits, where N c is the number of quark colors. In this paper, we show how one may remove the assumption of large N c and so begin investigation of N c =3 without soft-emission approximations. Treating finite … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…When combined with the leading-order rate Γ LO given by (3.7), we have 28) which indeed involves the same correction to [dΓ/dx] LO , and so toq, as (3.18).…”
Section: Double-log Correction For Shower Evolution Equationmentioning
confidence: 74%
See 1 more Smart Citation
“…When combined with the leading-order rate Γ LO given by (3.7), we have 28) which indeed involves the same correction to [dΓ/dx] LO , and so toq, as (3.18).…”
Section: Double-log Correction For Shower Evolution Equationmentioning
confidence: 74%
“…So there is no divergence of S NLO associated with x → 0 or x → 1. 28 In summary, the only IR divergences coming from S NLO are the uncanceled double-log divergences associated with y → 0.…”
Section: Jhep11(2020)053mentioning
confidence: 90%
“…Our calculation is also very pertinent for improving our understanding of color dynamics in the medium, for instance in the context of multi-gluon emissions with overlapping formation times [28] and to understand hadronization after exiting the QGP [29]. In the process of evaluation of the multi-Wilson line correlators, the only assumption made is the exact form of the medium average, see eq.…”
Section: Introductionmentioning
confidence: 99%
“…The quadratic Casimir operator, C 2 ≡ R a R a , commutes with all the su(N ) generators. 1 Hence in light of Schur's lemma, C 2 is proportional to the d × d identity matrix. In particular, the quadratic Casimir operator in the defining representation of su(N ) is given by…”
Section: The Defining Representation Of the Su(n) Lie Algebramentioning
confidence: 99%
“…Recently, two authors contacted me concerning a first draft of these notes, which they apparently found to be quite useful [1,2]. They urged me to make these notes more widely available, and I am pleased to accommodate their request.…”
mentioning
confidence: 99%